Hydrochemical indicators of water source and contamination in fen peatlands of varying hydrogeomorphic settings in northern and central Poland - Tatiana Solovey (Elsevier, 2021)
In this study, we considered 41 fens located in northern and central Poland. In our main hypothesis, we assumed that the base chemical composition of fen waters primarily depends on the hydrological regime, indicating a relationship to morphogenetic type of fen. We analyzed 40 physicochemical parameters of peatland porewater samples and discussed the relation of water chemistry with the hydrological and morphogenetic conditions of the individual fens. Further, we considered the additional factors that could significantly modify water chemistry. Physicochemical and hydrological parameters indicated a large diversity in habitat conditions among the investigated fens. Parameters significantly differentiating the examined objects were the concentrations of basic anions and cations and the associated electrolytic conductivity. Higher ion concentrations indicated a greater share of groundwater in the recharge of the investigated wetlands. Fens having a greater inflow of groundwater were characterized primarily by higher concentrations of calcium, bicarbonates and electrolytic conductivity, and were usually associated with tunnel and melt-out valleys. However, in some cases, the higher electrolytic conductivity resulted from anthropogenic pollution. Therefore, the use of indicators to separate such anthropogenically influenced sites from those naturally enriched in basic ions is crucial. Moreover, human-related disturbance of fen ecosystems were also demonstrated by elevated concentrations of certain metals and nutrients. We found that the processes responsible for the mobilization and inflow of metals played a secondary role in the diversification of the chemical composition of the waters of the investigated fens.